Can Environmental Governance and Corporate Performance be Balanced in the Context of Carbon Neutrality? — A Quasi-Natural Experiment of Central Environmental Inspections - Deng, Xiang; Huang, Benxin; Zheng, Qiuyan; Ren, Xiaohang (Frontiers in Energy Research, 2022)
This paper creatively studies the impact of the environmental governance on corporate performance in the context of China. We take the first round of central environmental inspections as the quasi-natural experiment shocks, and then test its effects on Chinese listed companies’ performance using the propensity score matching method (PSM) and the difference-in-differences (DID) with multiple periods method. Furthermore, we discuss the transmission mechanism between central environmental inspections and corporate performance. The results indicate that central environmental inspections have significantly improved the corporate performance of listed companies in polluting industries in the inspected provinces. The central environmental inspections reduce agency costs and enhance corporate performance by improving the internal agency problems of listed companies. In addition, state-owned and large-scale companies are more sensitive to the central environmental inspections, and the effect of corporate performance improvement is more obvious. However, in regions with different levels of environmental regulations, there is no significant difference in the effects of central environmental inspections on the improvement of corporate performance.